Assessing perceived participation among older adults total hip arthroplasty and total knee arthroplasty patients six months post-surgery: a cross-sectional study - Yao, Lifeng; Jia, Qin; Wu, Jiayun; Chai, Yufei; Gao, Chu; Wang, Yingying; Li, Ke; Lai, Meihong (Frontiers in Public Health, 2023)
This research sought to assess the perceived levels of participation and autonomy in senior patients who had received total hip arthroplasty (THA) or total knee arthroplasty (TKA) in Hangzhou, China. Furthermore, the study aimed to identify the factors linked to these outcomes.Study Design: This investigation will utilize a cross-sectional study design to assess perceived participation and autonomy among elderly total hip arthroplasty (THA) and total knee arthroplasty (TKA) patients. The research was conducted in Hangzhou, China, at a tertiary hospital. Methods: Convenient sampling was utilized to select 139 patients who underwent THA or TKA between March 2022 and March 2023 and met the inclusion criteria at a tertiary hospital in Hangzhou. The Impact on Participation and Autonomy Questionnaire, Hip/Knee Injury and Osteoarthritis Outcome Score (HOOS/KOOS), 5-Item Geriatric Depression Scale, Multidimensional Scale of Perceived Social Support, and Elders Health Empowerment Scale were used to assess perceived participation, hip/knee-related symptoms and functional restrictions, depression symptoms, social support, and health empowerment.The mean score for perceived participation and autonomy was 22.554 (SD: 13.042). The mean scores for participation in indoor autonomy, outdoor autonomy, family roles, and social relations were 0.654 (SD: 0.608), 1.324 (SD: 0.792), 1.053 (SD: 0.657), and 0.664 (SD: 0.542), respectively. Negative correlations were observed between perceived participation/autonomy scores and HOOS/KOOS, social support, and health empowerment scores. Conversely, a positive correlation was found between perceived participation/autonomy scores and depression scores. The detrimental effect of HOOS/KOOS, social support, and health empowerment scores on perceived participation and autonomy was notable, while the impact of depressive symptoms was comparatively minor. Conclusion: Older Chinese patients, at first six months post THA/TKA surgery, reported higher levels of perceived participation compared to individuals with other conditions, such as stroke patients. Functional limitations resulting from hip/knee-related symptoms, as well as social support and health empowerment, emerged as significant influencing factors for perceived participation and autonomy. This research enhances our comprehension of the elements influencing perceived participation among elderly individuals who have undergone THA/TKA procedures.